Peran Hedging dalam Membangun Citra Positif dalam Pidato Presiden AS - Rita Suswati; Dinda Khairani Pratiwi; Jessica Paskah Elizabeth Manullang; Nailah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Medan, 2024)
Hedging is an important rhetorical strategy in political discourse, used to show a degree of confidence and build a positive image of the leader, especially in US Presidential speeches from 1993 to 2021. The purpose of this study is to analyze the role of hedging in building a positive image and understand the variations of its use based on the political context and audience. The method used is a qualitative literature study, with secondary data analysis in the form of speech transcripts and related literature. The main findings show that the use of hedging varies between presidents, where Bill Clinton and Barack Obama use it to maintain credibility and reinforce commitments, while Donald Trump uses it less, but still in a diplomatic context. The research conclusion confirms that hedging has an important role in building a positive image of the leader but should be used with caution so as not to be misinterpreted as uncertainty.